12 Myocardial inflammation and diffuse fibrosis underpin the electrophysiological derangements of the ageing human heart–A CMR-ECGI study. (1st November 2021) - Webber, Matthew; Joy, George; Falconer, Debbie; Tao, Xuyuan; Pierce, Iain; Moon, James C; Hughes, Alun D; Lambiase, Pier D; Rudy, Yoram; Orini, Michele; Captur, Gabriella
Abstract : Background: Susceptibility to malignant ventricular arrhythmias can be predicted by activation recovery interval (ARI) and repolarisation time (RT) biomarkers noninvasively derived by electrocardiographic imaging (ECGI). The interaction between cardiac structural and electrophysiological changes during aging is unclear. We used our recently developed cardiovascular magnetic resonance (CMR)-ECGI vest to understand how the ageing myocardial substrate assessed by CMR interacts with these ECGI biomarkers under complete physiological conditions. Methods: CMR-ECGI at 3 Tesla was prospectively performed (figure 1 ). 256-Lead body surface potentials were recorded and co-registered with CMR-derived heart-torso geometries. Epicardial unipolar potentials were reconstructed using state-of-the-art ECGI algorithms to derive whole-heart electrophysiological maps (figure 2 ). Results: 45 Participants were recruited: 29 older persons from a population-based cohort (all 75 years; 55% male) and 16 young healthy volunteers (34±3 years, 62% male). Compared to young participants, older ones showed longer T1 (1300±38.4 ms vs 1280±46.5 ms, p =0.020) and T2 (46.1±0.06 ms vs 42.9±2.3 ms, p =0.001) and higher extracellular volume (ECV, 26.6±1.9% vs 22.6±3.5%, p <0.001). Activation time (AT) was prolonged in older compared to younger hearts (41.8±19.7 ms vs 36.8±20.0 ms, p =0.042) with similar but weaker trends observed for RT and ARI ( p =0.086, p =0.160). Apart from left ventricular ejection fraction (LVEF, e.g. for ARI β =1.9 ms [0.01–3.7] p =0.049), no other standard CMR size/function parameter or binary presence of late gadolinium enhancement, showed an association with ECGI parameters. By contrast, native T1, T2 and ECV were all associated with RT prolongation (respectively β =0.3 ms [95% confidence interval 0.01–0.64] p =0.048; β =6.0 ms [1.85–10.05] p =0.006; β =4.9 ms [0.22–9.60] p =0.041) and, T2 and ECV with ARI prolongation ( β =5.9 ms [1.88–9.92] p =0.005; β =4.8 ms [0.40–0.12] p =0.033). All associations persisted after adjusting for LVEF. Conclusion: The normal electrophysiological sequence of activation and repolarisation in the human heart changes markedly with ageing and may be explained by CMR-detected myocardial substrate changes consisting of low-grade inflammation and diffuse fibrosis. Our high-throughput and reusable CMR-ECGI solution has the ability to provide unprecedented insights into the pathophysiology of arrhythmogenesis beyond conventional measures of cardiac structure and function.